2017
DOI: 10.3892/ol.2017.7200
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of body weight loss and sarcopenia by a novel selective androgen receptor modulator in cancer cachexia models

Abstract: Abstract. Cancer cachexia is a syndrome that impairs the quality of life and overall survival of patients, and thus the effectiveness of anticancer agents. There are no effective therapies for cancer cachexia due to the complexity of the syndrome, and insufficient knowledge of its pathogenesis results in difficulty establishing appropriate animal models. Previously, promising results have been obtained in clinical trials using novel agents including the ghrelin receptor agonist anamorelin, and the selective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…In this study, the effective dose to increase BW by approximately 10% in monkeys was 10 mg/kg, and the AUC 0‐24h at 10 mg/kg was 8152 ng·h/mL. A dose of 0.3 mg/kg is sufficient to increase BW in rats . These findings indicate that monkeys required an approximately 30‐fold higher drug exposure to gain BW, compared with rats.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In this study, the effective dose to increase BW by approximately 10% in monkeys was 10 mg/kg, and the AUC 0‐24h at 10 mg/kg was 8152 ng·h/mL. A dose of 0.3 mg/kg is sufficient to increase BW in rats . These findings indicate that monkeys required an approximately 30‐fold higher drug exposure to gain BW, compared with rats.…”
Section: Discussionmentioning
confidence: 55%
“…We previously reported that SARM‐2f increased skeletal muscle weight with a much lesser effect on prostate weight . The mechanisms for tissue selectivity of SARM includes two factors: recruitment of specific cofactors to AR and a tissue‐specific cofactor expression profile .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations